Online Game Addiction Increases Risk of Violent Behaviour In Adolescents: Adiksi Game Online Meningkatkan Resiko Perilaku Kekerasan Pada Remaja - Nurhalimah; Belva Putri Sabila; Omi Haryati; Wartonah; Dinarti (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Aggressive behaviour in adolescents is closely related to online games. Addiction that occurs in adolescents will result inaggressive behaviour such as anger and hostility, which can hurt themselves and others. The research aims to analyzethe effect of online game addiction on violent behaviour in adolescents. This type of research, quantitative with crosssectional approach. The research population was all students of class X-XI at SMA Negeri 2 Tambun Utara. Samplingused a non-probability sampling technique, namely total sampling according to the inclusion criteria of 108 respondents.The measuring tool for determining the level of online game addiction uses the instrument Chen and Chang (2008), whilefor the aggressive level using the Aggression Questionnaire Scale (BPAQ) from Buss-Perry. Data analysis used isdescriptive statistical test and chi-square test. The most played type of online game is Mobile Legend (62.1%) with aplaying duration of 3 hours (62.1%) and most of the respondents (52.4%) have high aggressive behaviour. The results ofthe chi square test obtained p-value = 0.001 with ? = 0.05 (p-value <?), meaning that there is a significant relationshipbetween online game addiction and aggressive behaviour in students, with an OR of 3,770, which means that respondentswith high addiction have a 3.77 chance of highly aggressive behaviour compared to respondents with low addiction.